Assembly of a large cerium(iii)-containing tungstotellurites(iv) nanocluster: [Ce10Te8W88O298(OH)12(H2O)40]18−1. Issue 25 (7th July 2015) - Chen, Wei-Chao; Qin, Chao; Wang, Xin-Long; Li, Yang-Guang; Zang, Hong-Ying; Shao, Kui-Zhan; Su, Zhong-Min; Wang, En-Bo
<x xml:space="preserve">Abstract</x> The second largest lanthanide-containing tungstotellurites(iv) nanocluster Ce10Te8W88 was synthesized by combining cerium linkers and TeO32− heteroanion templates.